The Spanish Academic Collocation List - Eleonora Guzzi (Revista de Lingüística y Lenguas Aplicadas, 2025)
Phraseology plays a crucial role in academic texts, with collocation use key to demonstrating high competence in academic writing. Even for native speakers with limited experience in academic genres, academic collocations present challenges. Despite their importance, however, no sufficiently representative repertoire of academic collocations in Spanish has been developed as a resource for students, similar to those available for academic English. To address this gap, this article proposes a reference list of academic collocations in Spanish, designed for integrated in an academic writing tool and as a support for Spanish for Academic Purposes. Collocations were extracted from an academic corpus using NLP techniques and applying frequency and distribution criteria and Universal Dependency parsing. The resulting list was manually validated to ensure it includes useful collocations for Spanish students across various academic fields.